The Right to Belong, the Freedom to Stay. A Capabilities and Social Capital Analysis of Community-Based Integration Models in Southern Italy - Santamaria Amato,Giulia (2025)
This thesis contributes to ongoing debates on alternative models of refugee integration through a case study of Community-based Integration (CbI). As a participatory approach, CbI centers on social inclusion and community cohesion, expanding equitable access to opportunities for both refugees and locals. It has shown particular relevance in small towns and semi-rural areas affected by depopulation and economic stagnation, offering a locally grounded strategy for mutual renewal. Drawing on participant observation and semi-structured interviews, this research explores how both refugees and members of the host community are affected by the “EUROCOOP Jungi Mundu” project in Camini, Southern Italy. Using a combined Capability Approach and Social Capital Theory framework, the analysis shows how CbI strengthens refugees’ capabilities through everyday participation while contributing to revitalizing an inner area long shaped by demographic decline. By linking touristic revaluation with inclusion, Jungi Mundu has fostered new forms of care, interaction, and service provision. Yet, these efforts remain fragile, constrained by limited institutional support and broader structural precarity. The findings suggest that while CbI holds significant transformative potential, this is unlikely to be fully realized without stronger political recognition and long-term engagement from the State.
Keywords: Refugees; Integration; Community Participation; Capability Approach; Social Capital; Local Development; Southern Italy